BAGAIMANA PENERAPAN MARKETING DIGITAL DI UMKM? BIBLIOMETRIK ANALISIS - Wijayanto, Gatot (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Digital transformation has encouraged micro, small, and medium enterprises (MSMEs) to adopt digital marketing strategies in response to changes in consumer behavior and technological developments. This study aims to map trends, thematic focuses, and author collaborations in research related to digital marketing in MSMEs through a bibliometric approach. Data were collected from the Scopus database for the period 2000–2025 and analyzed using VOSviewer software to identify dominant keywords, topic clusters, author collaboration networks, and international cooperation. The results of the analysis show that the topics of digital marketing and MSMEs are the focus of discussion in the literature, with supporting themes such as e-commerce, social media, digital transformation, and marketing strategy. Meanwhile, author collaboration remains fragmented and predominantly local in nature. This study provides a theoretical contribution to strengthening the conceptual understanding of MSME digitalization, as well as offering practical implications for business actors and policymakers to design relevant and sustainable digital marketing strategies. This study also identifies limitations in the scope of the database and the depth of the content analyzed, thus recommending further research based on a qualitative approach or systematic review to complement these findings.